Struggle and success on the path to a positive reading identity: a collective case study of seventh-grade readers in a rural school - Tholstrup, Carrie B. (Kansas State University, 2022)
The more students read, the better they read, and students are more inclined to read when they are motivated to read. Students’ interests and their confidence as readers contribute to their motivation. Confidence is impacted by how students view themselves as readers, an identity which can be influenced by the environment surrounding them. The purpose of this narrative exploration of a collective case study was to identify how rural middle school students perceived themselves as readers and what factors in and outside of school shaped those perceptions. Five seventh-grade students and seven teachers in a rural PreK-12 school participated in this 13-week study. Data were collected using interviews, classroom observations, and email exchanges. Analysis revealed (a) student participants had potential to see themselves as readers which required ongoing support in and outside of the school setting throughout middle school; (b) students experience positioning, struggling, and succeeding as they construct their reading identities; (c) positive elementary experiences, focus on intrinsic motivation, schoolwide support for reading, and maintaining rigor while providing instruction in foundational elements all benefit the construction of positive reading identities. A small, rural school environment can provide conditions that support positive reading identity construction among its middle school students; however, teacher turnover and threat of closure can eclipse the impact of those conditions. Findings have implications for teachers who facilitate students’ reading identity construction. Implications for rural schools include meeting unique needs of middle school-aged students and connecting education to the community beyond the school walls.
Keywords: Reading; Rural; Middle school; Reading identity; Education